2021
DOI: 10.1590/2175-3369.013.e20210128
|View full text |Cite
|
Sign up to set email alerts
|

Caminata y vejez: explorando el espacio público peatonal de las personas mayores en los instrumentos de planificación urbana en Chile

Abstract: Resumen El envejecimiento es uno de los desafíos más relevantes que enfrentan las ciudades latinoamericanas, pero poco se conoce sobre cómo ese desafío es abordado por la planificación urbana. Este artículo busca avanzar en aquella discusión, indagando en cómo los instrumentos que definen el espacio público peatonal de las ciudades chilenas recogen las necesidades de las personas mayores y, en general, de los peatones. Con herramientas de análisis cualitativo, se estudiaron quince instrumentos normativos e ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Moreover, it would be relevant to examine how older people move and access opportunities individually, and to what extent their mobility is related to and motivated by their access to relevant services and equipment. Such analysis would benefit from the use of different research methods, be they walking interviews [29][30][31], apps [94], surveys [95], or measurements with GPS devices and accelerometers [96,97]. In general, it would be important to consider the access to healthy food as a multi-scale issue, involving not only the metropolitan scale here examined, but also neighborhoods and public spaces like streets and squares.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it would be relevant to examine how older people move and access opportunities individually, and to what extent their mobility is related to and motivated by their access to relevant services and equipment. Such analysis would benefit from the use of different research methods, be they walking interviews [29][30][31], apps [94], surveys [95], or measurements with GPS devices and accelerometers [96,97]. In general, it would be important to consider the access to healthy food as a multi-scale issue, involving not only the metropolitan scale here examined, but also neighborhoods and public spaces like streets and squares.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on these elements, this paper assesses walking access to street markets, considering their key role as a contributor to an urban population's urban well-being and especially to one of its fragile groups, such as older people. Our research has a geographical focus on Chile, a country where the population is rapidly ageing and elderly issues are gaining more attention, as well as in relation to urban mobility and the issues of urban justice that it raises [27][28][29][30][31]; despite this, public policies for ageing are only starting to be implemented [32]. Moreover, like many other Latin America countries, this is an ageing country with an unequal pension system, which makes it relevant for older people to access healthy and inexpensive food.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three participants walked at speeds below that average and seventeen above it (Table 1). In addition, thirty-two participants did not reach 0.9 m/s (3.2 km/h), which in Chile is the lowest designed walking speed for puffin and pelican crossings [66]. The interviewed older persons walked, on average, 2.53 km.…”
Section: Older Persons' Walking: Routes Destinies and Patternsmentioning
confidence: 92%
“…Inadequate pedestrian infrastructure (e.g., damaged, neglected and narrow sidewalks), absence of services (e.g., public toilets) and street furniture (e.g., benches) in the public space and lack of facilities in territories that are highly unequal have been described as common obstacles that older persons encounter in Chilean cities [60][61][62][63][64]. Likewise, it has also been suggested that the norms and devices (e.g., traffic lights) that regulate traffic have tended to be detrimental to pedestrians and have created a number of issues (e.g., short pedestrian crossing times) that can hinder older persons' trips [65][66][67]. After studying the hostile public spaces older persons face, some works have concluded that older persons are able to travel with relative normality in Chile because they have strong networks that provide support and not because of the amenities offered by its cities [25,68].…”
Section: Of 19mentioning
confidence: 99%
See 1 more Smart Citation